Electro-hydraulic drive of the variable ratio lifting device under active load - Kosucki, Andrzej (Strojniški vestnik, 2021)
Hydraulic systems fed by fixed displacement pumps driven by frequency-controlled electric motors can replace conventional throttling systems due to their ability to control the speed of hydraulic cylinders regardless of the value and direction of the load. These systems can improve the energy efficiency of the drive or even provide the possibility of energy recuperation during lowering. This paper presents experimental studies of the new drive system with volumetric control of the speed of the lifted/lowered payload using the example of a scissor lift. The system uses a reversible gear pump driven by an asynchronous motor fed by a frequency inverter operating in field-oriented control mode. Comparative studies of the mapping of the assumed speed of the hydraulic cylinder and platform are presented, as well as studies of the influence of the load change on the speed and positioning of the mechanism driven by the open-loop controlled system.
Keywords: črpalka z nastavljivo hitrostjo; dvigalni sistem; hidravlični pogoni; hydraulic drives; lifting systems; naprava z variabilnim razmerjem; speed controlled pumps; variable-ratio device